PREPARATION OF COMPATIBLE AND BIODEGRADABLE ACETYLATED CASSAVA STARCH/POLY (STYRENE-alt-MALEIC ANHYDRIDE) BLENDS USING POLYETHYLENE GLYCOL (400) AS PLASTICIZER (FUDMA JOURNAL OF SCIENCES, 2023)
The study was carried out to investigate the compatibility and biodegradability profile of acetylated cassava starch/poly(styrene-alt-maleic anhydride) blends using Polyethylene glycol (400) as plasticizer. Native cassava starch (NCS) was successfully acetylated at room temperature using acetic anhydride and 1M NaOH. The percentage acetylation and degree of substitution were found to be 5.38 % and 0.21 % respectively. Polymer blend films of Acetylated cassava starch (ACS) and poly (styrene-alt-maleic anhydride) (PSAMA) were prepared by casting technique. Biodegradation profile of the polymer film was evaluated by soil burial method and % water absorption of polymer blend were also determined as 1.31 % and 9.38 % respectively. Native cassava starch (NCS), acetylated starch (ACS) and their corresponding blends were further characterized by FTIR (CARY 630 AGILENT). The results obtained indicated an interaction between the two polymers. Scanning electron micrographs (SEM) of the polymer blend indicated a very good compatibility
Keywords: Acetylation, biodegradation, compatible, degree of substitution (DS)